Migrant mothers’ experiences of Caesarean section: a transcultural qualitative study - Rodriguez, Juliette; Moro, Marie Rose; Radjack, Rahmeth (Frontiers in Psychiatry, 2023)
Migrant women face an increased risk of adverse obstetrical outcome and Caesarean section. The psychological experience of Caesarean section combines physiological, social, and cultural dimensions. This qualitative study explores the subjective experiences of first-generation migrant women who gave birth by Caesarean section. Seven qualitative, semi-directed interviews were conducted from January to March 2022 in a Paris maternity hospital, with women in their postpartum period who had had a scheduled or emergency Caesarean section and straightforward obstetrical outcomes. The presence of an interpreter-mediator was systematically offered. Thematic analysis of the interviews was carried out following the Interpretative Phenomenological Analysis (IPA) methodology. Four themes were identified in the thematic analysis relating to the women’s experiences of Caesarean section: 1) The shock of the intervention combines disappointment, fear and early separation from the baby; 2) Pregnancy and delivery far from one's family aggravates the psychological suffering caused by isolation and loneliness related to migration; 3) The lack of cultural representations of Caesarean section leads to negative preconceptions and hinders mental preparation, in contrast with traditional or medicalised childbirth; 4) The women’s experiences of the medical follow-up highlights the importance of the continuity of care. Caesarean section, which is a physical break, re-enacts the symbolic break (cultural, social, familial) that follows on from emigration. Improvements in care include the need for a better preparation for Caesarean section, active efforts for care continuity, and the development of early prevention interviews and groups in maternity units.